MONITORING SUHU BODY TRANSFORMATOR BERBASIS SMS ( SHOT MESSAGE SERVICE ) PT. PLN AREA SURAKARTA - , SISWOYO; , Ir. Suyoto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report describes the body temperature of the transformer monitoring system based on SMS ( Short Message Service ) in the PT. PLN ( Persero ) Surakarta area using atmega16 microcontroler . Authors wanted to know whether the body temperature detector transformer using atmega16 this could help address concerns over the risks of explosion in the transformer due to excessive heat that can help maintenance of electrical equipment PLN . Existing data obtained through several phases through the observation phase , consultation and reference materials . The results obtained showed that the body temperature detector transformer using atmega16 works by detecting body temperature around the transformer , so the detection circuit using atmega16 will work when the sensor detects a temperature of the heat that exceeds the capacity of the transformer , when the sensor detects the temperature will exceed the capacity tansformator activate the modem as a transmitter in the form of SMS ( Short Message Service ).